Strategi Kampanye Sudrajat-Syaikhu Mendapat Dukungan Masa Populisme Islam Dalam Pilgub Jawa Barat 2018 - Djuyandi, Yusa; Riadi, Bagus; Ulhaq, Muhammad Zia; Drajat, Diki (Journal of Political Issues, 2019)
Islamic Populism has become a hot discussion in Indonesia after the emergence of the Ahok Phenomenon in the DKI Jakarta Election 2017. At that time, the period of Islamic populism which was disappointed with the system because it had created inequality vented his disappointment in a series of Islamic Defending I, II and III. The phenomenon of Islamic populism movements does not only occur in Jakarta, discussions of Islamic populism also develop in the constellation of the 2018 West Java Governor Election. One of the pairs of candidates who allegedly used the wave of Islamic populism was Sudrajat and Ahmad Syaikhu (Asyik). The pair carried by Gerindra and PKS benefited from getting a vote of Islamic populism because the Asyik bearer party was a party that got the image as a pro-Muslim party. But unfortunately this advantage has not been consolidated massively. 2019 hashtag presidential test taken by the Asyik pair in the second debate in the West Java Pilgub is believed to be one of the efforts to consolidate support for Islamic populism. In this paper, we will analyze how the strategy of the Fun couple to consolidate support from the previous period of Islamic populism in the case of the DKI Jakarta Pilkada, the period of Islamic populism in the ranks of Gerindra and PKS as the ruling opposition.